The Effect of Green Marketing and Brand Image on Consumer Buying Interest in MSMES in Palu City (Case Study in Chicken Bim) - Sitti Nur Fadillah; Sirajudin; Nasrulhak Akkas (Jurnal Sinar Manajemen, 2025)
The development of environmental issues and consumer awareness of sustainability encourages MSMEs to adopt green markpractices toes to attract buying interest. In Palu City, MSMEs such as Chicken Bim are starting to implement environmentally friendly strategies, such as the use of organic materials or biodegradable packaging, which can form a positive brand image. However, the extent to which green marketing and brand image affect consumer buying interest still needs to be further studied. This study aims to find out and analyze both simultaneously and partially the influence of green marketing and brand image on consumer buying interest in MSMEs in Palu City, especially in Chicken Bim. This research is a survey research type, whose samples are taken through purposive sampling techniques. Meanwhile, the respondents were Chicken Bim consumers who made takeaway or take-away purchases as many as 97 respondents. The method used is quantitative research using multiple linear regression analysis. The results of the study show that simultaneously there is a significant influence of green marketing and brand image on consumer buying interest in MSMEs in Palu City. Partially, there is a significant influence of green marketing on consumer buying interest in MSMEs in Palu City. Partially, there is a significant influence of brand image on consumer buying interest in MSMEs in Palu City.